A partially complete skeleton of Hippidion saldiasi Roth, 1899 (Mammalia: Perissodactyla) from the late Pleistocene of the high Andes in northern Chile. Issue 6 (10th December 2020) - Labarca, Rafael; Caro, Francisco J.; Villavicencio, Natalia A.; Capriles, José M.; Briones, Esteban; Latorre, Claudio; Santoro, Calogero M.
ABSTRACT: South America is well known for its abundance of Quaternary fossiliferous deposits, but well-preserved fossil remains from well-dated sites are scarce in the Atacama Desert and adjacent arid Andes. Here we report on a partially complete skeleton (46%) of a single young (ca. 3–4 years old) extinct horse discovered in the Salar de Surire, a salt flat located on the Andean altiplano of northern Chile (4, 250 m asl). Comparative and osteometric morphological analyses identify the specimen as a South American endemic horse Hippidion saldiasi Roth, 1899. A direct AMS radiocarbon date on bone collagen yielded a calibrated age of 13, 170 cal yr BP (2σ range: 13, 300–13, 060 cal yr BP) indicating that it lived near the end of the last glaciation. The body mass of the individual was calculated at approximately 326.4 kg, close to the upper limit of the larger sizes reported for the genus. Stable isotope evidence shows that the Salar de Surire horse relied on an almost 100% C3 diet that is mostly consistent with Hippidion specimens from other environments that also consumed either mixed C3/C4 or fully C3 diets. This finding is now the southernmost high-elevation record for this species and provides further evidence for the broad geographic and ecological distribution of this genus throughout southern South America.